2011
DOI: 10.1016/j.zool.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Bird terrestrial locomotion as revealed by 3D kinematics

Abstract: Most birds use at least two modes of locomotion: flying and walking (terrestrial locomotion). Whereas the wings and tail are used for flying, the legs are mainly used for walking. The role of other body segments remains, however, poorly understood. In this study, we examine the kinematics of the head, the trunk, and the legs during terrestrial locomotion in the quail (Coturnix coturnix). Despite the trunk representing about 70% of the total body mass, its function in locomotion has received little scientific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 33 publications
5
55
0
Order By: Relevance
“…A rather continuous increase in hip motions when increasing speed can be expected for birds of all sizes (see below). This is supported by further X-ray videographic data on quail recently published by Abourachid et al (Abourachid et al, 2011), who found hip extension during stance and whose overall results are consistent with our data on quail during slow locomotion.…”
Section: Methodology and Comparison Of Angular Valuessupporting
confidence: 93%
See 3 more Smart Citations
“…A rather continuous increase in hip motions when increasing speed can be expected for birds of all sizes (see below). This is supported by further X-ray videographic data on quail recently published by Abourachid et al (Abourachid et al, 2011), who found hip extension during stance and whose overall results are consistent with our data on quail during slow locomotion.…”
Section: Methodology and Comparison Of Angular Valuessupporting
confidence: 93%
“…Such a hip joint is also convenient for fulfilling other locomotor behaviors common for jackdaw, such as climbing into breeding burrows and chimneys or for diagonally walking on thin branches and manipulating items, etc. The relatively minute pelvic movements found in quail and tinamou in the present study have also been found in guinea fowl, ostrich and other quail individuals (Abourachid et al, 2011;Gatesy, 1999a;Rubenson et al, 2007). Locomotion with minute pelvic motions, as in grounddwellers and the rather waddling walk of Passeriformes or Anseriformes, do not represent different strategies of avian terrestrial locomotion.…”
Section: Medio-lateral Motions Of the Limb Pelvic Rotation And The Hsupporting
confidence: 71%
See 2 more Smart Citations
“…insects (Dangles et al, 2006;Wu et al, 2008;Nguyen et al, 2010;Truong et al, 2012); fish (Korff & Wainwright, 2004;Herrel et al, 2005;Huber et al, 2008;Wroe et al, 2008;Huber et al, 2009;Mara et al, 2009;Habegger et al, 2010;Tran et al, 2010); rodents (Bracha et al, 2003;Sakatani & Isa, 2004;Herbin et al, 2007;Morita et al, 2008;Beare et al, 2009;Fu et al, 2009;Stefen et al, 2011); reptiles (Deban & O'Reilly, 2005;Herrel & O'Reilly, 2006;Fuller et al, 2011;Schaerlaeken et al, 2011); birds (Westneat et al, 1993;Estrella & Masero, 2007;Abourachid et al, 2011;Dawson et al, 2011;Smith et al, 2011); as well as in humans (Arampatzis et al, 1999;Yoganandan et al, 2002;Imura et al, 2008;Shan, 2008;Bakker et al, 2009;Steeve, 2010). The main topics treated are flight features, bite force analysis, cognitive functions assessments by realtime tracking, anatomical and physiological study of locomotion, evaluation of mandibular motion and muscle activity during ingestion or vocalization, the effect of food type on feeding efficiency, 3-D bones reconstruction for motion morphology assessments, among others.…”
Section: The Study Of Biomechanics and Motion Analysismentioning
confidence: 99%